Some Methodological Features of Teaching the Subject «Higher Mathematics» in Higher Educational Institutions - Qosimova Makhbubakhon Yakubjanovna (Genius Journals, 2022)
This article discusses the training of modern specialists who meet modern requirements, the ability to build a mathematical model in the process, the use of modern technologies in obtaining solutions. The growth in the use of highly efficient technologies in production sets the task for teachers to prepare professionally competent, competitive specialists. The mechanism of constructing a mathematical model in solving problems, the use of the mathematical apparatus, the analysis of the results obtained, the use of the Maple software in solving the problem are considered
Keywords: Elastic beam; perforator; software system; quality of education